FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS TERHADAP IBU HAMIL DI RUMAH SAKIT UMUM DAERAH BENGKALIS - Alhidayati; Syukaisih; Amalia, Risa; Arisha, Popyana (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Abortion is the end of a pregnancy before the fetus is able to survive, namely when the gestational age has not reached 20 weeks or the fetus weighs <500 grams, either spontaneously or induced. Research objective to determine the relationship between age, education, profession, parity, knowledge, attitudes, family support and support from health workers on the incidence of abortion at the Bengkalis Regional General Hospital in 2023. This research is quantitative analytic with cross sectional research design. The population in this study were pregnant women who were treated at the Bengkalis regional general hospital from January to May, totaling 627 mothers. Simple random sampling technique with a total sample of 96 respondents. Measuring tool in data collection is a questionnaire. Data analysis with univariate and bivariate with chi-square. Research results show that there is a significant relationship between age and the incidence of abortion (P value = 0.004) OR = 0.263, there is a significant relationship between parity and the incidence of abortion (P value = 0.021) OR = 0.331, there is a significant relationship between attitude and the incidence of abortion ( P value = 0.000) OR = 0.161, there is a significant relationship between family support and abortion (P value = 0.048) OR = 0.192, there is a significant relationship between health worker support and abortion (P value = 0.021) OR = 0.159, none there is a significant relationship between education and abortion (P value = 0.139), there is no significant relationship between profession and abortion (P value = 1.000), there is no significant relationship between knowledge and abortion (P value = 0.528). It is hoped that the results of this study can be an illustration for health services to improve the quality of health, especially dealing with abortion cases.